Dietary Habits and Cooking Methods Could Reduce Avoidable Exposure to PCBs in Maternal and Cord Sera - Jin, Weiwei; Otake, Masae; Eguchi, Akifumi; Sakurai, Kenichi; Nakaoka, Hiroko; Watanabe, Masahiro; Todaka, Emiko; Mori, Chisato (Scientific reports, 2017)
Polychlorinated biphenyls (PCBs), like other persistent organic pollutants, are accumulating throughout the food chain and pose health threats to humans, especially children and foetuses. There is no protocol for reducing the contamination levels of the PCBs in humans. This study identified food items and cooking methods that reduce serum PCB levels by analysing data collected from the Chiba Study of Mother and Child Health. The sample size was 194 subjects. Serum PCB levels were measured using gas chromatography–electron capture negative ionization quadrupole mass spectrometry. Information on dietary habits was obtained from a brief diet history questionnaire that included questions about food items and cooking methods. Food items were categorized into food groups, and nutrient levels were calculated based on food item consumption. Principal component analysis and lasso regression were used as statistical methods. The analyses of food items and nutrients suggested that food items rich in dietary fibre reduce avoidable exposure to PCBs, as could grilling and deep frying of food, which could reduce avoidable exposure to serum PCBs in mothers and foetuses. (174 words).